Sp1 phosphorylation by ATM downregulates BER and promotes cell elimination in response to persistent DNA damage - Fletcher, Sally C (Nucleic Acids Res, 2018)
ATM (ataxia-telangiectasia mutated) is a central molecule for DNA quality control. Its activation by DNA damage promotes cell-cycle delay, which facilitates DNA repair prior to replication. On the other hand, persistent DNA damage has been implicated in ATM-dependent cell death via apoptosis; however, the mechanisms underlying this process remain elusive. Here we find that, in response to persistent DNA strand breaks, ATM phosphorylates transcription factor Sp1 and initiates its degradation. We show that Sp1 controls expression of the key base excision repair gene XRCC1, essential for DNA strand break repair. Therefore, degradation of Sp1 leads to a vicious cycle that involves suppression of DNA repair and further aggravation of the load of DNA damage. This activates transcription of pro-apoptotic genes and renders cells susceptible to elimination via both apoptosis and natural killer cells. These findings constitute a previously unrecognized ‘gatekeeper’ function of ATM as a detector of cells with persistent DNA damage.